Immunohistochemistry Evaluation of TGF-Î²1, SOX-9, Type II Collagen and Aggrecan in Cartilage Lesions Treated with Conditioned Medium of Umbilical Cord Mesencyhmal Stem Cells in Wistar Mice (Rattus novergicus) - Bintang Soetjahjo; Mohammad Hidayat; Hidayat Sujuti; Yuda Fibrianto (Journal of Tropical Life Science, 2018)
Currently, umbilical cord mesenchymal stem cells have the potential to be used as treatment options for any cartilage lesion. This research aimed to evaluate the effects of conditioned medium from umbilical cord mesenchymal stem cells (UC-MSC) on damaged cartilage through the expression of proteins TGF-Î²1, SOX-9, type II collagen and aggrecan, which are known to be related to chondrogenesis. UC-MSC were isolated from 19-days-pregnant Wistar mice and were cultured using the standard procedure to obtain 80% confluence. Subsequently, the culture was confirmed through a microscopic examination that was driven to be an embryoid body to obtain a pre-condition medium. This research utilized 3-month-old male Wistar mice and was categorized into 6 groups (3 control and 3 treatment groups). Each animal had surgery performed to create a femur condyle cartilage defect. The treatment groups were administered a dose of stem cells at 1 mL/kg. Next, immunohistochemical (IHC) staining was performed to examine the expression of TGF-Î²1, SOX-9, type II collagen and aggrecan in the 2nd, 3rd, and 4th month of evaluation. The results were analyzed statistically using ANOVA test. For each of the treatment groups, there was increased expression (p < 0.05) in all proteins TGF-Î²1, SOX-9, type II collagen and aggrecan when compared with control groups at the 2nd, 3rd, and 4th month of evaluation. Pre-conditioned medium from UC-MSC potentially increases the expression of TGF-Î²1, SOX-9, type II collagen and aggrecan in the damaged cartilage of Wistar mice.